2002
DOI: 10.1097/00063110-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Fatal intentional poisoning cases admitted to the University Hospitals of Leuven, Belgium from 1993 to 1996

Abstract: Between January 1993 and July 1996, a total of 2827 intentional cases of poisoning were registered in the University Hospitals of Leuven, Belgium. Ten of these cases were fatal. This study was set up to evaluate the substances involved, the circumstances, the features and the characteristics of the patients who died due to intentional poisoning. The male to female ratio of these fatal cases was 9 : 1. The median age was 43 years. Two groups of substances were revealed to be associated with fatal outcome. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 7 publications
2
20
0
Order By: Relevance
“…Male victim 367 (63.1%) outnumbered female 215 (36.9%) as males lead a more stressful life than female due to family responsibilities. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Maximum numbers of cases (32.2%) were in the age group 21-30 years due to the fact that at this period they are by nature more emotional, aggressive, intolerant and irrational. 14,15,19,21 Married outnumbered 413 (71%) single 142 (25%), because after marriage economic problem of family results in frequent quarrels and familial disharmony leading to increased stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Male victim 367 (63.1%) outnumbered female 215 (36.9%) as males lead a more stressful life than female due to family responsibilities. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] Maximum numbers of cases (32.2%) were in the age group 21-30 years due to the fact that at this period they are by nature more emotional, aggressive, intolerant and irrational. 14,15,19,21 Married outnumbered 413 (71%) single 142 (25%), because after marriage economic problem of family results in frequent quarrels and familial disharmony leading to increased stress.…”
Section: Discussionmentioning
confidence: 99%
“…14,15,19,21 Married outnumbered 413 (71%) single 142 (25%), because after marriage economic problem of family results in frequent quarrels and familial disharmony leading to increased stress. [6][7][8][9][10][11][12][13][14][15][16][17][18] Maximum numbers (27.6%) of victims were educated up to high school level. In our study maximum number of poisoning death have been reported in the month of June (14.4%) followed by March (13.5%).…”
Section: Discussionmentioning
confidence: 99%
“…Pesticides act as a common agent for suicidal purpose after trivial family problems and in developing countries kill around 3,00,000 people each year [2][3][4] . Suicidal death in industrialized countries are also caused by pesticide ingestion 5,6 . Poisoning cases can also occur accidentally and rarely as homicidal purpose.…”
mentioning
confidence: 99%
“…Although PQ poisoning of humans is still reported in many countries (Bruyndonckx et al 2002;Hwang et al 2002;Hsu et al 2003;LugoVallin et al 2003), there are no effective antidotes and no measures to enhance the elimination of PQ from the body (Jaeger et al 1995). As described above, chymase may contribute both directly and indirectly to fibrotic changes.…”
Section: Discussionmentioning
confidence: 99%